AN ANALYSIS OF COMMISSIVE SPEECH ACT IN MOVIE ENTITLED CINDERELLA - Mellynea Kezyta Nugraheni; Kristina Maya Iriana Sari (Universitas Katolik Widya Mandala Surabaya, 2022)
The purposes of this study were to describe the types of commissive speech acts, and to describe how commissive speech acts used in the movie. This study was a descriptive-qualitative research. This research focused on commissive speech act expressed by the characters found in the movie. The step to get the data is collecting the data from the script of Cinderella movie which contain commissive speech act, reading the dialogue, and classifying the data based on the types of commissive speech act based on Searle and Vanderveken (1985) categories. The next step is classifying non verbal communication. Then, the use of commissive speech act was analyzed within the pragmatics framework. The types of commissive speech act found in Cinderella movie are refuse, threaten, promise, accept, offer, bet, commit, consent, and assure. Â Keywords: Speech Acts; Commissive; Pragmatics